2005
DOI: 10.1103/physreve.71.046129
|View full text |Cite
|
Sign up to set email alerts
|

Exact kinetics of the sol-gel transition

Abstract: The formation of a gel in a disperse system wherein binary coagulation alone governs the temporal changes of particle mass spectra is studied under the assumption that the coagulation kernel is proportional to the product of masses of coalescing particles. This model is known to reveal the sol-gel transition, i.e., the formation of one giant cluster with the mass comparable to the total mass of the whole system. This paper reports on the exact solution of this model for a finite total mass of the coagulating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…This happens when any higher moment (n 2) in series (2.5) diverges [5], for instance when M 2 diverges (tends to infinity) as time approaches some finite value t g termed the gelation point (Refs. [5,[8][9][10]). As indicated in the Introduction, kernel (1.2) represents a positive homogeneous function of degree λ = 4/3.…”
Section: Inertial Turbulent Coagulationmentioning
confidence: 97%
See 1 more Smart Citation
“…This happens when any higher moment (n 2) in series (2.5) diverges [5], for instance when M 2 diverges (tends to infinity) as time approaches some finite value t g termed the gelation point (Refs. [5,[8][9][10]). As indicated in the Introduction, kernel (1.2) represents a positive homogeneous function of degree λ = 4/3.…”
Section: Inertial Turbulent Coagulationmentioning
confidence: 97%
“…Gelation had been shown to occur in polymerization processes (Drake [3], Ziff [4], Hendriks et al [5], Rotstein et al [6]) and during formation of needlelike aerosol particles in external electric fields (Lushnikov and Piskunov [7], Lushnikov [8]). In both cases the kernel is proportional to the product of masses of coagulating particles,…”
Section: Introductionmentioning
confidence: 99%
“…This is the well-known, phasetransition-like behavior that occurs when a sol becomes a gel, i.e. at gelation [8][9][10] . This few in number, large in mass population are the superaggregates with their hybrid morphology displayed in Figs.…”
Section: In 3d Space the Number Of Monomers In A Volume With Radius Rmentioning
confidence: 99%
“…Although this phase-transition-like behavior can result from the kinetics of simple binary collisions 8,9 , it has been rigorously connected to a thermodynamic functional 10 . A complete description of gelation would incorporate the relevant aspects of both descriptions.…”
Section: Introductionmentioning
confidence: 99%
“…The coagulation in the system with the kernel = was analyzed by Lushnikov [1978Lushnikov [ , 2004Lushnikov [ , 2005 who showed that a gel should form from coagulating sol after a finite interval of time. Experimentally this process was observed by Lushnikov et al [1990 who supposed that the dipoledipole interaction of FA is responsible for this phenomenon.…”
Section: Aerosol-aerogel Transitionmentioning
confidence: 99%